Falta de aplicación de la normativa en procesos de terminacion de la unión de hecho - Plaza Rodríguez, Jeanneth del Rocío; Lanche Chuquimarca, Carla Selene (Machala: Universidad Tecnica de Machala, 2016)
La Unión de Hecho es una de las formas de convivencia humana más antigua, conocida como Concubinato, con el devenir del tiempo se han ido superando criterios de que la unión de hecho es contraria a las buenas costumbres y a la moral, hoy se las ha reconocido socialmente, siendo varios los factores que motivan a dos personas a vivir juntas sin que intervenga el matrimonio, entre tales factores de orden económico, ideológico, cultural, religioso, etc., de manera que ya no existe la diferenciación entre familia legítima e ilegítima, pues su concepción jurídica ha cambiado notablemente. Para nadie es desconocido el avance que ha tenido la unión libre, desplazando en cierta forma al matrimonio. Nuestro Código Civil y la Constitución de la República del Ecuador vigente desde el 2008 en su artículo 68 el cual contempla esta unión cuando han transcurrido más de dos años de convivencia ininterrumpida, siempre que los convivientes estén libres de vínculo matrimonial, con las mismas consecuencias y efectos legales que el matrimonio, por tanto se forman derechos y obligaciones para la pareja y la protección necesaria a los hijos dentro de esta unión. Además dicho artículo aumentó la protección jurídica de las uniones de hecho, ya que reconoce que puede formarse no solamente por un hombre y una mujer, sino por parejas del mismo sexo, lo que constituye una reforma sustancial. A la presente fecha se han logrado grandes avances acerca de este tema, sin embargo existen vacíos legales que dan lugar a la inseguridad jurídica en cuanto a la declaratoria de la Unión de Hecho, lo que no sucede con el matrimonio legalmente constituido, siendo necesario legislar precautelando el interés de los núcleos familiares constituidos mediante la figura jurídica de la Unión de Hecho.
The Union of Fact is one of the oldest forms of human coexistence, known as Cohabitation; with the passage of time have been overcome criteria that the informal union is contrary to good morals and morality, today they have been socially recognized, with several factors that motivate two people to live together without involving marriage, among such factors economic, ideological, cultural, religion, etc., so that there is no differentiation between legitimate and illegitimate family, because his legal concept has changed markedly. Is no stranger the progress that has had the cohabiting, displacing somewhat the marriage. Our Civil Code and the Constitution of the Republic of Ecuador in force since 2008, in its Article 68 includes this union when more than two years of uninterrupted cohabitation have elapsed, provided that the cohabitants are free from marriage, with the same consequences and legal effects as marriage, for both rights and obligations are formed for the couple and necessary protection to children within this union. Besides that article increased the legal protection of Union of Fact, recognizing that can be formed not only by a man and a woman, also by same-sex couples, which constitutes a substantial reform. To this date we have made great progress on this issue, but there are loopholes that give rise to legal uncertainty regarding the declaration of the Union of Fact, which does not happen with the marriage legally constituted, being necessary to legislate safeguarding the interest of households constituted by the legal form of the Union of Fact. In other words, there is a lack of applicability and the procedure to follow, when the judge of the Judicial Unit of the Family, Women, Children and Adolescents unilaterally request the termination of the Informal Union, since the law It provides only that the defendant be notified three times, in person or by ballot, causing the defenselessness of the counterparty, since it does not determine the citation by the press in case of absence and opening the case to trial; so this research aims to set the "gaps" through the analysis of two cases in particular, existing in legislation and establish the various criteria of the guarantors of justice when issuing the Auto Qualifying request termination of the Union of Fact and if possible bring reforms to the Civil Code, including a paragraph or unnumbered article that states that procedure or that the same rules of termination of marriage are followed.
Keywords: UNION DE HECHO; VACIO LEGAL; DERECHO; INSEGURIDAD JURIDICA; NOTIFICACION